Advancing Language Teaching and Revolutionizing the Educational Experience - Malikovna, Kiyasova Ra’no (Journal of Innovation in Education and Social Research, 2025)
This article explores how language teaching can be advanced and the educational experience revolutionized through modern technologies and innovative pedagogical methods. It highlights the integration of digital tools such as AI, virtual reality, and language learning platforms, which can provide personalized and interactive learning experiences. The article also examines key pedagogical approaches like Task-Based Language Learning, Communicative Language Teaching, and the flipped classroom model, emphasizing their relevance in today’s educational landscape. Additionally, it discusses the importance of cultural immersion, multimodal learning, and fostering a mindset of lifelong learning to ensure the continuous growth of language skills.